Chatbot Gamifikasi sebagai Media Pembelajaran Interaktif: Kajian Grounded Theory - Ramadhan, Hafizh (Jurnal Profesi Insinyur Universitas Lampung, 2025)
Chatbots are automated conversational systems utilized across various fields to provide information services and digital interaction. The integration of gamification within chatbots has emerged as an approach to enhance user motivation and engagement through game-based mechanisms. However, studies examining how users respond to and experience interactions with gamified chatbots remain limited. This research aims to analyze literature related to human interaction with gamified chatbots using a Grounded Theory approach. The analysis stages were carried out through article selection and coding processes to identify key themes and patterns. The findings indicate that gamification elements have a positive influence on user motivation, engagement, and perception. These results highlight the potential of gamified chatbots as an effective medium for digital interaction and provide a foundation for future system development and further research.